2012
DOI: 10.1097/ico.0b013e31823f8b2a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transcutaneous Electrical Stimulation on Rabbit Corneal Epithelial Cell Migration

Abstract: The transcutaneous application of electrical stimulation can considerably increase the rate of corneal healing, especially in the first 24 hours of healing full surface corneal abrasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Different groups of cells, including neural crest cells ( 34 , 35 ), fibroblasts ( 33 ), neurons ( 36 , 37 ), and CECs ( 38 40 ), respond to electric fields by directed migration or directed growth in vitro . This has been shown to increase the rate of cornea healing in cornea abrasions in a vivo model of corneal wound healing in rabbits ( 10 ). It is also hypothesized that QMR can stimulate the lacrimal system, reactivate the lacrimal and meibomian gland tissue and benefit the ocular annexes ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different groups of cells, including neural crest cells ( 34 , 35 ), fibroblasts ( 33 ), neurons ( 36 , 37 ), and CECs ( 38 40 ), respond to electric fields by directed migration or directed growth in vitro . This has been shown to increase the rate of cornea healing in cornea abrasions in a vivo model of corneal wound healing in rabbits ( 10 ). It is also hypothesized that QMR can stimulate the lacrimal system, reactivate the lacrimal and meibomian gland tissue and benefit the ocular annexes ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of matrix metalloproteinase and the infiltration of leukocytes were reduced, supporting an anti-inflammatory effect ( 5 ). Electrical stimulation has been hypothesized to affect cell migration and proliferation ( 7 10 ), and accelerate nerve regeneration via the promotion of neurotrophic factors such as brain-derived neurotrophic factor and nerve growth factor with the influx of calcium into neurons ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…While no studies have reported on an ICT modality for ocular pain, we found four reports describing the use of TENS in the setting of ocular pathology and two that studied the effects of TENS in ocular pain (33)(34)(35)(36). Although the latter two reported pain relief, the first of these investigated the more invasive subcutaneous application of electrical current and the second from 1991 involved only ten cases in the setting of acute surgical pain (33,34).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic therapy with an extremely low-frequency electromagnetic frequency complements is a noninvasive, safe, and simple method for healing injuries from a variety of causes (6). Ghaffarieh et al discovered that magnetic treatment of corneal chemical burns significantly reduced the ulcerative area when compared to control groups, particularly in the first week of therapy, and that its effectiveness was comparable to medical therapy (12). The success of a single case report is, of course, limited, and it is critical to confirm the current findings with additional findings from additional studies.…”
Section: Discussionmentioning
confidence: 99%